Current market demand for core competencies of librarianship-a text mining study of american library association's advertisements from 2009 through 2014 - Yang, Qinghong; Zhang, Xingzhi; Du, Xiaoping; Bielefield, Arlene; Liu, Yan Quan (Applied Sciences-Basel, 2016)
As librarianship evolves, it is important to examine the changes that have taken place in professional requirements. To provide an understanding of the current market demand for core competencies of librarianship, this article conducts a semi-automatic methodology to analyze job advertisements (ads) posted on the American Library Association (ALA) Joblist from 2009 through 2014. There is evidence that the ability to solve unexpected complex problems and to provide superior customer service gained increasing importance for librarians during those years. The authors contend that the findings in this report question the status quo of core competencies of librarianship in the US job market.
23 citations (Crossref) [2023-10-31] tex.article-number: 48 tex.unique-id: ISI:000371827200001
Keywords: Competency; Job advertisement; Librarianship; Text mining; dept.ils; peer-reviewed